Pengaruh Promosi, Lokasi Dan Kualitas Pelayanan Terhadap Keputusan Menginap Di Selyca Mulia Hotel Samarinda - Frannanda Clara Sri Sepvia Haling (Fakultas Ilmu Sosial dan Ilmu Politik, Universitas Mulawarman, 2022)
The purpose of this study was 1) to determine the effect of promotion, location and service quality simultaneously and partially on the decision to stay at Selyca Mulia Hotel Samarinda. 2) to find out which one has the most influence on the decision to stay at Selyca Mulia Hotel Samarinda. This research was conducted at Selyca Mulia Hotel Samarinda which is located on Jl. Bhayangkara No.58 Bugis, Samarinda City. This research is a type of quantitative research. The population of this study were guests of Selyca Mulia Hotel Samarinda. And the sample amounted to 100 respondents. The analysis technique used is validity test, reliability test, classical assumption test, multiple linear regression analysis, hypothesis testing. The results showed that the promotion variable (X1), location (X2), service quality (X3) simultaneously affected the decision to stay (Y). This is evidenced by F count = 45.591 > 3.09 and sig value 0.000 < 0.05. In the results of the t test, the service quality variable (X3) partially affects the decision to stay (Y). This is evidenced by the t arithmetic (X3) 0.000 <0.05 and the t-count value = 7.692 > T table 1.984. The test results of the most influential variable is the service quality variable (X1) with a result of 0.579. It is recommended to Selyca Mulia Hotel Samarinda to be able to improve the quality of service with fast, agile and consistent service, polite, responsive and agile employees as well as employees who have communication skills and mastery of employee knowledge about hotel products.